Analysis of salvage operation in head and neck microsurgical reconstruction - Hyodo, Ikuo; Nakayama, Bin; Kato, Hisakazu; Hasegawa, Yasuhisa; Ogawa, Tetsuya; Terada, Akihiro; Torii, Shuhei (The Laryngoscope, 2007)
In this study, we examined salvage operations after reexploration in head and neck reconstruction and analyzed ways to solve problems. Free flap reconstruction of the head and neck lesion was carried out for 513 cases in our hospital over the past 12 years. Twenty-one cases of reexploration were caused by postoperative thrombosis (4.1%). We could only salvage seven cases (33.3%) of 21 cases from flap thrombosis. All seven cases were included in the category of venous thrombosis, and they were undertaken within 3 days postoperatively. Our results have shown that once thrombosis occurs, there is little possibility of flap salvage, particularly 3 days after operation and in infectious cases. When no flow phenomena are observed and no flap salvage is deemed possible, aggressive treatment such as a second free flap or next pedicle flap should be chosen as soon as possible to avoid any delay in postoperative treatment.